534. CHEMORADIOTHERAPY FOR ESOPHAGEAL CANCER: DO WOMEN RESPOND BETTER THAN MEN?. (24th September 2022) - Abdulrahman, Maan; Abdulrahman, Rand; Kumar, Nitya; Corbally, Martin; Walsh, Thomas
Abstract: The incidence of esophageal cancer is higher in men, with evidence that men present at a more advanced stage. Randomized trials of neoadjuvant treatments have hitherto not stratified for gender, but it is unclear whether the response to neoadjuvant chemoradiotherapy (NeoCR) and outcome is similar for both genders. The aim of this study is to compare presentation, response to treatment and survival of esophageal cancer between men and women. A prospectively maintained database of 205 patients (143 males; 70%) diagnosed with esophageal carcinoma and treated with curative intent (definitive chemoradiotherapy, neo-adjuvant chemoradiotherapy followed by surgery or surveillance, or surgery alone), between 1998 and 2019 at one teaching hospital, was interrogated for impact of gender on response to treatment (complete versus incomplete clinical response) and survival. Of 36 females who had NeoCR, 28 (78%) had a complete clinical response, compared to 52 of 116 males (45%). The complete pathological response rate was 21 of 36 (58.3%) of females compared to 31% of men (P<0.001). Controlling for age, stage at diagnosis, and type of therapy, females survived significantly longer than males [HR 0.72 CI 0.53-0.98 (p=0.038)]. Our results suggest a gender difference in response to chemoradiotherapy, which is reflected in outcome and survival. It is suggested that future randomized trials of neoadjuvant and indeed adjuvant therapy stratify for gender which may impact on management guidelines.